Effects of polyol excipient stability during storage and use on the quality of biopharmaceutical formulations - Min-Fei Sun; Jia-Ning Liao; Zhen-Yi Jing; Han Gao; Bin-Bin Shen; You-Fu Xu; Wei-Jie Fang (Elsevier, 2022)
Biopharmaceuticals are formulated using a variety of excipients to maintain their storage stability. However, some excipients are prone to degradation during repeated use and/or improper storage, and the impurities generated by their degradation are easily overlooked by end users and are usually not strictly monitored, affecting the stability of biopharmaceuticals. In this study, we evaluated the degradation profile of polyol excipient glycerol during repeated use and improper storage and identified an unprecedented cyclic ketal impurity using gas chromatography with mass spectrometry (GC-MS). The other polyol excipient, mannitol, was much more stable than glycerol. The effects of degraded glycerol and mannitol on the stability of the model biopharmaceutical pentapeptide, thymopentin, were also evaluated. The thymopentin content was only 66.4% in the thymopentin formulations with degraded glycerol, compared to 95.8% in other formulations after the stress test. Most glycerol impurities (i.e., aldehydes and ketones) reacted with thymopentin, affecting the stability of thymopentin formulations. In conclusion, this work suggests that more attention should be paid to the quality changes of excipients during repeated use and storage. Additional testing of excipient stability under real or accelerated conditions by manufacturers would help avoid unexpected and painful results.